Autonomous industrial assembly using force, torque, and RGB-D sensing. (17th April 2020) - Watson, James; Miller, Austin; Correll, Nikolaus
ABSTRACT: We present algorithms and results for a robotic manipulation system that was designed to be easily programable and adaptable to various tasks common to industrial setting, which is inspired by the Industrial Assembly Challenge at the 2018 World Robotics Summit in Tokyo. This challenge included assembly of standard, commercially available industrial parts into 2D and 3D assemblies. We demonstrate three tasks that can be classified into 'peg-in-hole' and 'hole-on-peg' tasks and identify two canonical algorithms: spiral-based search and tilting insertion. Both algorithms use hand-coded thresholds in the force and torque domains to detect critical points in the assembly. After briefly summarizing the state of the art in research, we describe the strategy and approach utilized by the tested system, how it's design bears on its performance, statistics on 20 experimental trials for each task, lessons learned during the development of the system, and open research challenges that still remain. GRAPHICAL ABSTRACT: